Eleições no Porto e em Gondomar : da Monarquia para a República - Cruz, Maria Antonieta (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Studying comparatively the municipal elections of the city of Porto, urban space, Gondomar, rural space contiguous to the Northern capital, and Vila Real, a space that is also rural but with the specificities that derive from the connection with Port wine production, one intends to add a contribution to the study of the electoral geography, seeking to highlight the legislative repercussions in the formation of the elector and eligible bodies. We will also analyse the profile of the elected and their suitability for the goals of the community that elect them.